Efektivitas Kampanye Media sosial dalam Mempengaruhi Persepsi dan Perilaku Pengguna Rokok Elektrik - Nurmidin, M Fadhel (Universitas Negeri Gorontalo, 2024)
The use of electronic cigarettes among teenagers and young adults is increasing, raising concerns about health risks and potential addiction. This study aims to analyze the effectiveness of social media campaigns in shaping perceptions and influencing the behavior of e-cigarette users. The research employs a literature review method, examining relevant studies published in the last five years. The findings indicate that social media plays a significant role in raising awareness about the dangers of e-cigarettes. Social factors, such as peer influence and family environment, are key determinants in an individual's decision to use e-cigarettes. Additionally, the low level of user awareness regarding health risks highlights the need for stronger education-based campaign strategies. Optimally utilizing social media with evidence-based content and targeted approaches can help reduce the prevalence of e-cigarette use. Government regulations and community-based interventions are also necessary to enhance the effectiveness of these campaigns. With a comprehensive approach, social media campaigns have great potential to change perceptions and behaviors related to e-cigarette use, thereby contributing to improved public health awareness.